(untitled) (Biocenosis, 2026)
The global environmental crisis poses one of the greatest contemporary challenges for humanity and requires profound transformations in educational systems. At the same time, artificial intelligence (AI) stands out as one of the most influential technologies of the 21st century, with the potential to reshape teaching and learning processes. This essay analyzes the relationship between environmental education and AI, highlighting the opportunities, risks, and perspectives. It concludes that, if applied ethically and with a sustainability- oriented approach, AI can strengthen environmental education by improving access to information, personalizing learning, simulating environmental phenomena, and supporting data-driven decision-making. Nevertheless, it warns of the need to consider its ecological impact, ethical implications, and technological equity so as to ensure truly sustainable education.